ANALISIS KESULITAN BELAJAR SISWA KELAS IV SD 104221 PANCUR BATU DALAM MEMAHAMI KONSEP PECAHAN SENILAI - Chairunnisa Warda; Umar Darwis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the learning difficulties experienced by fourth-grade students at SD 104221 Pancur Batu in understanding the concept of equivalent fractions. The research used a descriptive qualitative method with data collection techniques including observation, interviews, and questionnaires. The findings revealed that most students face difficulties in understanding equivalent fractions, primarily due to internal factors such as health issues, intelligence, interest, and low learning motivation. External factors, including limited family support, inadequate school facilities, and lack of varied teaching media, also contribute to the low level of comprehension. Based on the findings, collaborative efforts among teachers, parents, and the school are needed to create a more supportive and enjoyable learning environment, along with the use of innovative teaching methods and media.